2016
DOI: 10.1177/0021998316669856
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and thermal properties of nanocomposites based on chiral poly(ester-imide) matrix reinforced by vitamin B1 functionalized multiwalled carbon nanotubes

Abstract: Chemical functionalization of carboxylated multiwalled carbon nanotubes with vitamin B1 was carried out under ultrasonic irradiation. The functionalized nanotubes were embedded in a chiral and biodegradable poly(ester-imide) to prepare multiwalled carbon nanotubes reinforced polymer nanocomposites. Optically active poly(ester-imide) was synthesized by step-growth polymerization of aromatic diol and amino acid based diacid. The vitamin B1 functionalized multiwalled carbon nanotubes and the resulting nanocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Poltavets et al [101] synthesized docetaxel-loaded PLGA nanoparticles with a folate modification via an emulsion solvent-evaporation. The in vitro study revealed these nanoparticles performed non-functionalized nanoparticles and free docetaxel in vitro anticancer activities against HeLa cervical carcinoma cells [104].…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Poltavets et al [101] synthesized docetaxel-loaded PLGA nanoparticles with a folate modification via an emulsion solvent-evaporation. The in vitro study revealed these nanoparticles performed non-functionalized nanoparticles and free docetaxel in vitro anticancer activities against HeLa cervical carcinoma cells [104].…”
Section: Othersmentioning
confidence: 99%
“…To improve the reinforcing effect of CNTs in polymer nanocomposites, good dispersion and effective interfacial adhesion between CNTs and the polymer matrix are required (NCs). However, it takes some effort to disperse effectively the CNTs in the composites due to ¶- ¶ interactions and strong van der Waals forces between the tubes that cause CNT aggregation in the composites [94]. Therefore, CNT hybrids are used to aid CNTs in disperse inside polymer matrices [95].…”
Section: Othersmentioning
confidence: 99%
“…Recently, many researchers have reported the use of MIT for the functionalization of MWCNTs using amino acids, vitamins, epoxy compounds, proteins, and polymers [ 41 , 42 ]. Overall, MIT-based functional techniques are easy, effective, and completed in a single-step process, and they increase the magnitude of functionalization and binding in MWCNTs.…”
Section: Microwave Irradiation-based Development Of Mwcntsmentioning
confidence: 99%